Marcadores moleculares na análise de espécies e composição populacional de peixes marinhos de recifes de corais da família Pomacanthidae (Perciformes) - Affonso, Paulo Roberto Antunes de Mello (2004)
The Brazilian coast extends over nearly 8,000km. Along the coastline, several marine ecosystems can be found and determine a rich ichthyofauna, regarding both diversity and number of species. The reef sites are characterized as the main reason for such abundance. As a paradox, genetic studies aiming to characterize the several species and populations from this environment are nearly absent in Brazil. Based on these statements, the major goals of the present work were to analyze the population structure and the relationship among marine fish species from a Perciform family, common at coral reefs and important for aquarium trade Pomacanthidae. The selected species were Centropyge aurantonotus, Holacanthus ciliaris, H. tricolor, Pomacanthus arcuatus and P. paru, distributed over nearly all the Brazilian shore, besides another species from the family Chaetodontidae, closely related to that focused in this work - Chaetodon striatus. For that, molecular markers obtained from analyses of genomic DNA by RAPD and microsatellites were adopted. The results based on RAPD profiles, from a set of primers, indicate that species from both families show a high genetic variability, with inter-specific and inter-populational differences. Specific marks were found in all species, useful for the establishment of phylogenetic relationships and taxonomical discrimination. The dendrogram generated allowed to distinguish each species, revealing that those from a same genus are more closely related. Albeit the values of gene flow and genetic identity were relatively high after inter-populational comparisons, indications of structuring along the Brazilian Province were detected, particularly if we consider φs t values. The most conspicuous species along the coast, composing widely distributed populations, tended to exhibit greater genetic similarities among samples. Animals from oceanic isolates were not quite differentiated from inshore populations, but showed decreased variability. The isolation and characterization of microsatellites in the species P. paru and H. ciliaris, according to PIMA (PCR isolation of microsatellite arrays) methodology, allowed us to select several microsatellite loci, useful for populational approaches. Primers flanking such regions were designed and it was verified that one locus, called Pp02 was polymorphic and it is present in Pomacanthus and Holacanthus representatives. The populational analyses of the locus Pp02 in P. paru revealed significant values of Fst and genetic differentiation, in agreement with population structure hypothesis. These data, described for the first time, are useful for the conservation management of such exploited animals and for the inferences of dispersal and populational composition of reef species from the Brazilian Province.